Determinan Nilai Perusahaan Manufaktur pada Indeks Saham Syariah Indonesia - Fifi Afiyanti Tripuspitorini; Iwan Setiawan; Mochamad Edman Syarief; Setiawan Setiawan; Aditya Dais Gumara; Tiara Putie Purwitasari (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
This study aims to determine the effect of financial performance consisting of Total Assets Turnover (TATO), Current Ratio (CR), Return on Assets (ROA), Debt to Equity Ratio (DER), and macroeconomic factors consisting of inflation, interest rates, and the exchange rate against the value of manufacturing companies on the Indonesian Sharia Stock Index (ISSI) for the 2016-2020 period. Firm value variable is proxied using Tobin's Q ratio. The research method used is descriptive-quantitative method using multiple linear regression analysis techniques. The research object used is financial performance, macroeconomic factors, and the value of manufacturing companies with secondary data derived from data from the Indonesia Stock Exchange (IDX), the Central Statistics Agency (BPS), Bank Indonesia, and the Financial Services Authority (OJK). The research subjects used are manufacturing companies that are included in ISSI with a total sample of 76 companies that have met the criteria for selecting samples using the purposive sampling method. Hypothesis testing was carried out by path analysis using the WarpPLS 7.0 program. The results showed that TATO, ROA, and interest rates had a significant positive effect on the value of manufacturing companies listed on ISSI; CR, DER, and the dollar exchange rate have a significant negative effect on the value of manufacturing companies listed on ISSI; and inflation has no effect on the value of manufacturing companies listed on ISSI.